2020
DOI: 10.1371/journal.pone.0239655
|View full text |Cite
|
Sign up to set email alerts
|

Time to recovery and predictors of severe community-acquired pneumonia among pediatric patients in Debre Markos referral hospital, North West Ethiopia: A retrospective follow-up study

Abstract: Introduction Globally, pneumonia is a major cause of morbidity and mortality among children which leads to over 156 million episodes and 14.9 million hospitalizations each year. Besides this fact, the recovery time and predictors of children's hospitalization related to severe communityacquired pneumonia is not well known. Therefore, the aim of this study was to estimate the median time to recovery and its predictors among severe community-acquired pneumonia patients admitted to the pediatric ward, Debre Marko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
30
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(46 citation statements)
references
References 12 publications
13
30
3
Order By: Relevance
“…32 The CDC's higher estimation of length of hospital stay could be because they estimated for all children under the age of 15 years. Studies conducted in University of Gondar Comprehensive Specialized Hospital, Northern Ethiopia (3 days) 30 Hospital (4 days) 31 found nearly similar median time to recover. But the median time to recovery in this study was higher than the finding in Nepal (2 days), 11 and lower than findings reported by two studies conducted in Tanzania (6 and 10 days).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…32 The CDC's higher estimation of length of hospital stay could be because they estimated for all children under the age of 15 years. Studies conducted in University of Gondar Comprehensive Specialized Hospital, Northern Ethiopia (3 days) 30 Hospital (4 days) 31 found nearly similar median time to recover. But the median time to recovery in this study was higher than the finding in Nepal (2 days), 11 and lower than findings reported by two studies conducted in Tanzania (6 and 10 days).…”
Section: Discussionmentioning
confidence: 83%
“…This finding is higher than the incidence density of recovery in University of Gondar Comprehensive Specialized Hospital, 30 Debre Markos Referral Hospital. 31 The difference in the quality of services and time when the studies were conducted may explain the discrepancy among studies. The two studies were conducted earlier than this study, over time, there could have been differences in treatment protocol, service quality, and in availability of medical equipment.…”
Section: Discussionmentioning
confidence: 99%
“…Dependent variable. Co-morbidity:-Any disease condition (acute or chronic) present during admission in addition to SCAP (29). .…”
Section: Study Variablesmentioning
confidence: 99%
“…Time to seeking care: -Children getting care with in < 5 days after getting sick are considered as early presenters while those children getting care after ≥5 days are considered as late presenters (29).…”
Section: Study Variablesmentioning
confidence: 99%
See 1 more Smart Citation